PEMANFAATAN CANGKANG BIJI KARET DAN (Havea brasiliensis) DAN CANGKANG KEMIRI (Aleurites moluccana) SEBAGAI BAHAN BAKU BIOBRIKET - I Ketut Suka Astawan; Lya Agustina; Susi Susi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
Biobriquette a solid fuel that can be used as an alternative energy source that has a certain shape, Manufacture biobriket from agricultural waste shell rubber seeds and shell hazelnut can be done by adding adhesive, where the raw materials charred beforehand then crushed, mixed adhesives, printed by the system hydraulic or manual, and then dried. This research was conducted with two factor randomized block design (RBD) first factor comparison Biobriquette making material (rubber seed shells and shells Pecan) and the second factor is the adhesive tapioca konsentration (8%, 10% and 12%) 15 combination trials with replications per 2 times to obtain 30 units experimental unit. The  best treatment results in this study produced a 30:70 ratio between the shell and the shell pecan rubber seed with adhesive concentration of 10% which resulted in calorific value of 6609.32 Cal / g, 3.90% moisture content and ash content of 6.10%.